2005
DOI: 10.1183/09031936.05.10087304
|View full text |Cite
|
Sign up to set email alerts
|

Lung function in adults with cystic fibrosis at altitude: impact on air travel

Abstract: Current guidelines for air travel state that patients with chronic respiratory diseases are required to use oxygen if their in-flight arterial oxygen tensions (Pa,O 2 ) drop below 6.6 kPa. This recommendation may not be strictly applicable to cystic fibrosis patients, who may tolerate lower Pa,O 2 for several hours without clinical symptoms.Lung function, symptoms, blood gas levels and signs of pulmonary hypertension were studied in 36 cystic fibrosis patients at altitudes of 530 m and, after 7 h, 2,650 m. A h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 27 publications
2
40
0
3
Order By: Relevance
“…The large number of UK centres that took part and of patients recruited suggests, as previously noted, that potential problems associated with respiratory disease and air travel are well recognised [8], as is the need for more substantial evidence on which to base future recommendations. With a few exceptions [9][10][11][12], previous studies aimed at determining risk in adult passengers have examined small numbers of patients with COPD [13][14][15][16][17][18][19][20][21][22] in the acute setting. They have largely excluded comorbidity and studied stable patients.…”
Section: Discussionmentioning
confidence: 99%
“…The large number of UK centres that took part and of patients recruited suggests, as previously noted, that potential problems associated with respiratory disease and air travel are well recognised [8], as is the need for more substantial evidence on which to base future recommendations. With a few exceptions [9][10][11][12], previous studies aimed at determining risk in adult passengers have examined small numbers of patients with COPD [13][14][15][16][17][18][19][20][21][22] in the acute setting. They have largely excluded comorbidity and studied stable patients.…”
Section: Discussionmentioning
confidence: 99%
“…FISCHER et al [151] reported small but statistically significant increases in the FEV1 and FVC at 2,650 m while THEWS et al [152] reported no change and ROSE et al [153] demonstrated a slight drop in these values at 3,000 m.…”
Section: Cystic Fibrosismentioning
confidence: 99%
“…ROSE et al [153] studied 10 patients in a hypobaric chamber and found that the average Pa,O 2 fell from a baseline value of 10.6 kPa (79.5 mmHg) at sea level to 8.0 kPa (60 mmHg) and 6.05 kPa (45.5 mmHg) at simulated altitudes of 2,000 m and 3,000 m, respectively. FISCHER et al [151] took 36 patients to an actual altitude of 2,650 m for a period of 7 h and found that the median Pa,O 2 fell from 9.8 kPa (74 mmHg) at 530 m to 7.1 kPa (53 mmHg) at that altitude. The data also suggest that the more severe the underlying lung disease, the greater the likelihood of significant hypoxaemia; six out of their 11 patients with an FEV1 ,50% predicted sustained a fall in resting Pa,O 2 to ,6.7 kPa (50 mmHg) at 2,650 m, whereas only four of the 20 patients with an FEV1 .70% predicted experienced a similar change.…”
Section: Cystic Fibrosismentioning
confidence: 99%
“…AKERØ et al [22] investigated hypoxia in a group of patients with COPD during a 6-hour commercial flight, and found that there was an initial fall in Pa,O 2 once the flight had reached cruising altitude, which was maintained throughout the flight. FISCHER et al [23] have studied hypoxia in patients with cystic fibrosis at low altitude (530 metres) and after 7 hours at high altitude (2,650 metres). In this study, patients were hypoxic at altitude, but there was no trend to worsening with time and few reported any additional symptoms.…”
Section: Methods Of Predicting Hypoxiamentioning
confidence: 99%